ANALISIS STRATEGI PENGEMBANGAN WARALABA KULINER DALAM PERSPEKTIF ISLAM (STUDI KASUS KEDAI COGER) - Muhammad Erlangga Subirawan (2020)
Franchise is a form of partnership in the management of the culinary business. Under Islamic economics, franchise system is identically similar to Syirkah. Kedai Coger is a chain of coffee shops that applies partnership within Syirkah Mudharabah contracts. This research is a qualitative descriptive form with SWOT analysis and will be conducted on Bandung. Depok, Tangerang in West Java and Senayan, Jakarta. The results of this study are Kedai Coger which uses a business system franchise has fulfilled the mechanism and franchise relationship although with certain differences, along with the application of franchising in Islam. In developing its franchise, Kedai Coger has also implemented a marketing mix strategy that emphasizes product, price, place and promotion. In addition, Kedai Coger has tried to carry out its business in accordance with Islamic principles.